Range size and abundance dynamics of Japanese breeding birds over 40 years suggest a potential crisis in warm areas - Yuichi Yamaura; Kazuhiro Kawamura; Masayuki Senzaki; Munehiro Kitazawa; Isao Nishiumi; Naoki Katayama; Tatsuya Amano; Yasushi Ishigooka; Shigeto Sudo; Takeshi Osawa; Mutsuyuki Ueta (Scientific Reports)
Abstract Understanding the current status of biodiversity is crucial to preventing its loss in a changing world. We examined changes in the geographical range size and abundance of 165 bird species breeding in Japan during the past 40 years, as well as temperature niche changes in the past 20 years. Higher temperatures were recorded within the ranges of non-native species than in those of native species, and we detected range-size expansion and increased abundance among non-native species. Although open-land species exhibited range reductions from the 1970s to the 1990s, many recovered and the ranges of only a few species declined after this period. Nevertheless, the abundance of open-land species did decline, despite range-size recovery; similar inconsistencies were detected for waterbirds and raptors. Analysis of long-term temperatures suggested that species left warmest areas within their distributions while maximum temperatures experienced by species during the survey years did not change systematically. Birds in warm regions may be facing a crisis, with attrition of native bird communities and expansion of non-native species. It is necessary to establish efficient measures to prevent further expansions of non-native species and conservation measures of native species within managed areas in warm regions with few intact habitats.